Reaksi Pasar Modal Indonesia Terhadap Bencana Banjir Tahun 2007 dan 2013 di Daerah Khusus Ibukota (DKI) Jakarta (Studi Peristiwa pada Sembilan Sektor Industri Terdaftar di BEI) - INDRACARA, Acintya ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Flood event in Daerah Khusus Ibukota (DKI) Jakarta is a natural disaster which is often repeated and supposedly has a five-year cycle of its occurrence. However this event cannot be anticipated or predicted accurately related to the timing of the flood in Jakarta. Flood has caused financial losses to many casualties especially for the inhabitants of Jakarta city and its surrounding regions. Stability of the countryâs economic growth in Indonesia which includes consumption level, investment, government spending, and export-import are also disrupted because of DKI Jakarta as the capital city of Indonesia, which serves as the center of government, business and financial center, and also investment center, was flooded. The flood event in Jakarta underlying this research that using event study approach to examine the information content of an event. The purpose of this study is to observe the reaction of the nine industry sectors listed on the Indonesia Stock Exchange and classified based on JASICA (Jakarta Stock Industrial Classification), which include: agriculture